KESIAPAN MAHASISWA KEPERAWATAN KOTA BANDA ACEH DALAM MELAKUKAN PERTOLONGAN PERTAMA PADA FRAKTUR - Salsabila, Safina; Jufrizal, Jufrizal; Aklima, Aklima (Juru Rawat. Jurnal Update Keperawatan, 2025)
The incident of fracture in Indonesia are still very high. Aceh is listed as one of the provinces with a high  incidence of fractures in indonesia. The main thing when a fracture occurs is to provide first ai quickly and  immediately. Therefore, the readiness of the people especially nursing student to provide appropriate first  aid is crucial to prevent more severe injuries or even death. This study aims to determine the readiness of  nursing students in Banda Aceh to provide first aid for fractures. The method of this research is quantitative  with a descriptive approach. The population of this study is nursing students in Banda Aceh. The sample size  of 163 students selected using total sampling technique. Data processing was univariate analysis. The results  showed that 161 respondents (98.8%) was considered ready to provide first aid for fractures, and 2 respondents (1.2%) was considered sufficiently ready to provide first aid for fractures. The conclusion that the majority of respondents in this study express high readiness to provide first aid for fractures when viewed from both cognitive and affective domains. Recommendation for the future researchers to conduct more in-  depth studies regarding readiness as observed from the psychomotor domain or directly observe respondents  readiness when encountering fracture victims